2019
DOI: 10.1111/ene.14006
|View full text |Cite
|
Sign up to set email alerts
|

The risk of recurrent stroke at 24 months in patients with symptomatic carotid near‐occlusion: results from CAOS, a multicentre registry study

Abstract: Background and purpose The risk of recurrent stroke amongst patients with symptomatic carotid near‐occlusion (SCNO) has not been clearly established, and its management remains controversial. The aim was to define the 24‐month risk of recurrent stroke and to analyse the effect of the different treatment modalities (medical treatment and revascularization) in a population of patients with SCNO. Methods A multicentre, nationwide, prospective study from January 2010 to May 2016 was performed. Patients with angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As the difference between near-occlusion and conventional stenosis is management-altering according to current guidelines [4,5], improvements in carotid ultrasound methods are needed if carotid ultrasound is to retain this prominent role. Also, the role of ultrasound might change in the future because recent studies reveal that some near-occlusions might benefit from revascularization [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…As the difference between near-occlusion and conventional stenosis is management-altering according to current guidelines [4,5], improvements in carotid ultrasound methods are needed if carotid ultrasound is to retain this prominent role. Also, the role of ultrasound might change in the future because recent studies reveal that some near-occlusions might benefit from revascularization [22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…A lack of awareness and/or lack of attention to detail leads to symptomatic near-occlusions misdiagnosed as conventional stenosis which, by current guidelines [4,5], would result in unnecessary treatments. Recent non-randomized evidence has challenged these guidelines [2,[15][16][17][18][19][20][21][22], why further studies and trials might prove superiority of other management strategies. Improved diagnostics may enhance future clinical studies and allow for implementation of findings.…”
Section: Discussionmentioning
confidence: 99%
“…The CAOS study methodology has been described previously. 20 The study population comprised adult patients with an angiography-confirmed diagnosis of atherosclerotic CNO and ipsilateral ischemic stroke, TIA, or retinal ischemia in the previous 6 months. This study was supported by the "Stroke Project" initiative of the Spanish Cerebrovascular Diseases Study Group and obtained ethics approval from "Comité de Ética e investigación Clínica Hospital General Universitario Gregorio Marañón," with ID number of the approval: 122/09.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%